ANALISIS PENDAPATAN PETANI CABAI MERAH DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Saputra, Riki; Malik, Adlaida; Ulma, Riri Oktari (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This research was conducted in the Kumpeh Subdistrict, Muaro Jambi Regency. The study was conducted using a survey method and sampling was carried out on the sample farmer groups. The research objective is to determine the income and the contribution of red chilli farming to the income of farmers. The results of the study found that the average income of red chilli farming in Maju Jaya Village, Kumpeh District was Rp. 40,353,243 per hectare with an average cost of farming a red chili pepper Rp.18,412,535 per hectare. There are five business patterns in the red chilli farm that is cultivated by sample farmers in Maju Jaya Village, Kumpeh District. The average income of red chilli farming for each business pattern is that in business pattern I is Rp. 5,441,957 per month, in business pattern II is Rp. 5,646,574 per month, in business pattern III is Rp. 5,904,642 per month, in business pattern IV is Rp. 6,542,844 per month, and in business pattern V of Rp 3,993,654 per month. While the contribution of red chilli farming income to the lowest income of farmers is in business pattern I, namely red chilli farming and oil palm farming. The contribution of red chilli farming income to farmers' income during the red chilli planting season is in business pattern I of 45.2%, in pattern II of 72.8%, in business pattern III of 71.7%, in business pattern IV of 70, 8%, and the business pattern V is 69.9%. This shows that the red chili farming contributes greatly to the income of farmers in Maju Jaya Village, Kumpeh District.